Zika virus dysregulates human Sertoli cell proteins involved in spermatogenesis with little effect on tight junctions. - Mahamud-Ur Rashid; Ali Zahedi-Amiri; Kathleen K M Glover; Ang Gao; Michaela E Nickol; Jason Kindrachuk; John A Wilkins; Kevin M Coombs (Public Library of Science (PLoS), 2020)
Zika virus (ZIKV), a neglected tropical disease until its re-emergence in 2007, causes microcephaly in infants and Guillain-Barré syndrome in adults. Its re-emergence and spread to more than 80 countries led the World Health Organization in 2016 to declare a Public Health Emergency. ZIKV is mainly transmitted by mosquitos, but can persist in infected human male semen for prolonged periods and may be sexually transmitted. Testicular Sertoli cells support ZIKV replication and may be a reservoir for persistent ZIKV infection. Electrical impedance analyses indicated ZIKV infection rapidly disrupted Vero cell monolayers but had little effect upon human Sertoli cells (HSerC). We determined ZIKV-induced proteomic changes in HSerC using an aptamer-based multiplexed technique (SOMAscan) targeting >1300 human proteins. ZIKV infection caused differential expression of 299 proteins during three different time points, including 5 days after infection. Dysregulated proteins are involved in different bio-functions, including cell death and survival, cell cycle, maintenance of cellular function, cell signaling, cellular assembly, morphology, movement, molecular transport, and immune response. Many signaling pathways important for maintenance of HSerC function and spermatogenesis were highly dysregulated. These included IL-6, IGF1, EGF, NF-κB, PPAR, ERK/MAPK, and growth hormone signaling. Down-regulation of the PPAR signaling pathway might impact cellular energy supplies. Upstream molecule analysis also indicated microRNAs involved in germ cell development were downregulated by infection. Overall, this study leads to a better understanding of Sertoli cellular mechanisms used by ZIKV during persistent infection and possible ZIKV impacts on spermatogenesis.